2021
DOI: 10.1029/2020ja029091
|View full text |Cite
|
Sign up to set email alerts
|

Evening Side EMIC Waves and Related Proton Precipitation Induced by a Substorm

Abstract: Electromagnetic ion cyclotron (EMIC) waves in the magnetosphere are known to be generated by the cyclotron instability of anisotropic distributions of energetic (1-100 keV) protons (e.g., Kennel & Petschek, 1966;Sagdeev & Shafranov, 1961) constituting the ring current and plasma sheet populations. The growth rate of the instability is determined by the magnetic field strength, hot proton flux, energy, temperature anisotropy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 111 publications
(179 reference statements)
0
21
0
Order By: Relevance
“…The above analysis focused on the IB location determined based on proton flux observations of only one energy channel (i.e., 39 keV). However, the scattering and subsequent precipitation due to FLCS are energy‐dependent (Yahnin et al., 2021; Yu et al., 2020; Yue et al., 2014; Zhang et al., 2010). Therefore, we further utilize the higher energy channel data (i.e., 115 keV) on POES satellites to conduct the same analysis and yield empirical formulas for the IB location at different energies.…”
Section: Resultsmentioning
confidence: 99%
“…The above analysis focused on the IB location determined based on proton flux observations of only one energy channel (i.e., 39 keV). However, the scattering and subsequent precipitation due to FLCS are energy‐dependent (Yahnin et al., 2021; Yu et al., 2020; Yue et al., 2014; Zhang et al., 2010). Therefore, we further utilize the higher energy channel data (i.e., 115 keV) on POES satellites to conduct the same analysis and yield empirical formulas for the IB location at different energies.…”
Section: Resultsmentioning
confidence: 99%
“…Yahnin et al. (2021) examined a non‐storm EMIC event but it was related to a substorm event, thus, not strictly quiet time event. They showed that the proton flux enhancement coincided with EMIC wave enhancement or appearance.…”
Section: Discussionmentioning
confidence: 99%
“…The wave growth rates and cut-off frequencies of each sub-band are determined by the hot ion temperature anisotropy, ion composition, and cold plasma density (Kozyra et al, 1984). As the EMIC wave instability evolves, the initially unstable proton distribution isotropizes due to pitch-angle scattering and loss of protons into the atmosphere (e.g., Usanova et al, 2010;Søraas et al, 2013;Yahnin et al, 2021). This process is incorporated in global ring current models (Jordanova et al, 2012) which showed its contribution to a gradual recovery of magnetic storms.…”
Section: How Do Ulf Waves Couple To the Ring Current?mentioning
confidence: 99%